Decision-making Approach to Employee Selection among Companies in Malaysia - Koh, Anna Ching Ling (2013)
With so much rhetoric placed on the importance of “hiring the right employee” in every organization to ensure a ‘fit’ between the potential candidates and the company as a wrong hire could amount up to 30% of the employee’s earning in the first-year to an organization (Hacker, 1997). This topic – employee selection has received little attention in the Malaysian context, therefore, this research was conducted with the main objective to study organizations hiring or selection methodology, the analytic/ rational or intuitive/ social approach they choose in reaching a final hiring judgment, the issues and challenges that they faced, as well as their future strategy among organizations in Malaysia. The limitations within selection’s decision-making due to humans’ subjectivity are known as bounded-rationality is also explored in this research. A total of 50 surveys were carried out among companies from various industries, and 3 interviews were conducted with senior human resource personnel of varying company size and industry in relation to the subject of decision-making approaches to selection among organizations in Malaysia. The key findings of this research suggest that the majority of Malaysian organizations neither wholeheartedly accept nor reject an analytic/ rational approach but favors a hybridization approach to selection where there is a blending of both analytic and intuitive model which provides an acceptably holistic approach in their hiring judgment. There are, however, a haphazard way in the practice of an analytic/ rational approach which could be improved on. Perhaps, organizations in Malaysia could adopt a more rigorous scientific-based selection process as a compliment to the preferred intuitive/ social approach in their decision-making.